Manajemen Sarana dan Prasarana Pendidikan dalam Pembelajaran di Madrasah Tsanawiyah - Parno; Rahayuningsih , Retno (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to analyze the management of educational facilities and infrastructure in MTsN 10 Boyolali in supporting the learning process. The focus of the study includes five main aspects of management, namely planning, procurement, inventory, maintenance, and removal. This study uses a descriptive qualitative approach with data collection methods through interviews, observations, and documentation. The results of the study show that facility planning is carried out through an analysis of priority needs adjusted to budget capabilities. The procurement of facilities is sourced from BOS funds, community contributions, and third-party assistance, which allows madrasas to meet most of the learning needs. Inventory is carried out periodically to maintain asset control, while daily and periodic maintenance is sought to maintain the condition of the facility. The removal of facilities is carried out according to procedures to reduce the burden of maintenance costs. The obstacles faced include budget limitations, limited land area, and difficulties in scheduling maintenance without disrupting the learning process. However, the madrasah made various improvement efforts, including increasing funding sources through partnerships, space optimization, and more planned maintenance scheduling. Overall, the management of facilities and infrastructure at MTsN 10 Boyolali has been running according to procedures and providing significant support for learning effectiveness, although it still needs improvement in several aspects to achieve more optimal service quality